The Capacity to Integrate and Deal with Environmental Issues in Local Transport Policy and Planning - Hansen, Jahn (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
The approach of this study has been to describe and analyse how environmental objectives and strategies have materialised in the real-life context of local transport policies and plans, how environmental perspectives have been picked up by policymakers concerned with transport issues, how policy and planning processes have been affected, etc. Focus has been on the actual practices of transport policy making and planning from an environmental perspective in Lund, Groningen, and Aalborg. The primary research aim has been to identify and discuss the capacity to integrate and deal with environmental issues in local transport policy-making and planning processes. This is a summary of the lessons learned from the comparative study consisting of the cases of Lund, Groningen, and Aalborg. The summary primarily focuses on the main lessons to be learned among policy and planning practitioners.